ANIMATION VIDEOS : ITS EFFECTS ON STUDENTS’ WRITING ABILITY - Eva Faliyanti; Yasmika Baihaqi; Nita Mulyani (Universitas Muhammadiyah Metro, 2023)
The aim of this research is to find out the effect and significant difference of using animation video on the students’ writing ability of eleventh graders at MAN 1 Metro. This research is using quantitative research. The researcher took 76 students among 152 students as sample of the research. The sample for experimental group is XI IPA 3 and for control group is XI IPA 4. The result of the computations as follow: 1) the mean of students ​​in pre-test of experimental group is 63.03 and the control group is 63.47. 2) the mean of the students in post-test of the experimental group is 71.08 and the control group is 66.55. It means that there is significant difference on students’ writing ability by using animation video at the eleventh grade of MAN 1 Metro. From the computation showed that the t-value is higher than t-table is 2.235> 0.677 and Sig.(2-tailed) is lower that 0.05 (0.028< 0.005). It can be concluded that there is influence of using animation video in teaching writing of the eleventh grade at MAN 1 Metro in the academic year 2021/2022.